Pengaruh Disposisi Matematis terhadap Kemampuan Penalaran Matematis Peserta Didik pada Materi Sistem Persamaan Linear Dua Variabel - Yuliany, Nur; Hairunnisa, Saskia; Baharuddin; Sulasteri, Sri (Alauddin Journal of Mathematics Education, 2024)
This study aims to find out: (1) the description of students' mathematical reasoning ability on the material of the two-variable linear equation system, (2) the description of the mathematical reasoning ability of students on the material of the two-variable linear equation system, (3) the influence of mathematical disposition on the mathematical reasoning ability of students on the material of the two-variable linear equation system at SMP Negeri 49 Makassar. This study uses an ex post facto type of research with a quantitative approach. This research was carried out at SMP Negeri 49 Makassar with a population of 136 students in grade VIII which was divided into 5 classes, while the sample from this study amounted to 102 students who were selected using a simple random sampling technique. The instruments used in this study are questionnaires for mathematical dispositions and tests for mathematical reasoning skills. The data analysis techniques used are descriptive statistics and inferential statistics in the form of simple linear regression tests. The results of this study show that (1) the mathematical disposition of grade VIII students of SMP Negeri 49 Makassar is in the medium category. (2) the mathematical reasoning ability of grade VIII students of SMP Negeri 49 Makassar is in the medium category. (3) Based on the partial hypothesis test for the mathematical disposition variable, the value of t-calculation was obtained. (3,493) >,t-table. (1.98) so that it can be concluded that the mathematical disposition variable has a significant effect on the mathematical reasoning ability of students in the material of the two-variable linear equation system at SMP Negeri 49 Makassar.